Capitalism without conscience (2013)
How could one not remember The Prisoner – the cult British 60s series in which a giant bubble frantically chased the hero played by Patrick McGoohan? These days, our world is in a similar situation – each and every one of us are hostages of bubbles because the world is full of them, and not just from the speculative bubbles that plague our markets. Indeed, there is nothing easier than differentiating the bubble that imprisons and isolates our politicians, the salary and bonuses bubble for the executive managers of large companies and in the finance world, the youth unemployment bubble, and finally the inequality bubble. Just like the bubble that tirelessly chased the prisoner of our TV series, it would seem that our financial system has been affected by a similar curse because the collapse of a bubble displaces like clockwork the speculative fever of another instrument or another market, which then blows up to make another speculative bubble! Indeed, financially we are progressively losing control of our lives. It wasn’t for any reason that Joseph Stiglitz, the Nobel prize winner in Economics, questioned whether or not a person’s life nowadays depends on “their income or the education provided by their parents”.